The Gln15Arg mutation in the transcriptional factor PALM1 produces multifoliate alfalfa - Gomez, Maria Cristina; Jozefkowicz, Cintia; Mozzicafreddo, Matteo; Odorizzi, Ariel; Arolfo, Valeria; Basigalup, Daniel Horacio; Ayub, Nicolás Daniel; Soto, Gabriela Cynthia (Springer, 2022)
The CRISPR/Cas9 system has proven to be highly valuable for genome editing in several important crops, including the allogamous tetraploid cultivated alfalfa (Medicago sativa). However, the fact that most of the beneficial mutations relevant to alfalfa breeding programs are recessive mutations identified in the autogamous diploid species Medicago truncatula is a limitation. Naturally, the identification of dominant mutations can overcome this constraint and maximize the benefits of genome editing. In this article, we present the identification of a novel dominant mutation producing multifoliate leaves. Specifically, we showed that the mutation of the conserved glutamine 15 of the transcriptional factor PALM1 to arginine produces heptafoliate leaves in alfalfa, improving its digestibility and nutritional quality. Finally, we discuss the potential use of this mutation to rapidly generate transgenic-free legume forages with higher nutritional value via adenine base editors.